Quantitative Evaluation of Systems 11th International Conference, QEST 2014, Florence, Italy, September 8-10, 2014, Proceedings - Norman, Gethin; Sanders, William (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the proceedings of the 11th International Conference on Quantitative Evaluation of Systems, QEST 2014, held in Florence, Italy, in September 2014. The 24 full papers and 5 short papers included in this volume were carefully reviewed and selected from 61 submissions. They are organized in topical sections named: Kronecker and product form methods; hybrid systems; mean field/population analysis; models and tools; simulation; queueing, debugging and tools; process algebra and equivalences; automata and Markov process theory; applications, theory and tools; and probabilistic model checking.